Integração de contextos e habilidades pessoais, sociais e profissionais no desenvolvimento de soluções tecnológicas para o profissional da saúde - Abib, Janaina Cintra (Universidade Federal de São Carlos, 2016)
This thesis presents a research behind the creation of a process model for application development and a set of guidelines to instruct and support the work of developers focused on healthcare. The current Brazilian condition reflects that the working environment of healthcare professionals in long term care is conducive to the construction of a new identity and reference for these professionals, who incorporate their personal and social activities to professional activities and build cooperative relations with their peers beyond the professional environment. In this context, where healthcare professionals are re-analyzing their relationship with work and issues that affect the quality of life and the quality of their professional activities, the support of technological resources is a strong partner, especially in sharing and disclosure information and also in management daily tasks. In order to incorporate technology requirements that naturally may be included in the workflow of these professionals without interrupt their routines, software developers have been mobilized to create natural interaction applications that help healthcare professionals and promotes the adoption of applications. Natural interactions are defined here as the way users share information using technological resources and applications instinctively, in a transparent way, without concern the peculiarities of the application or technological appeal. For the development of these applications, which considers users’ profiles who naturally mix professional, personal and social contexts, it is required a process model to guide and assist developers in this task. Thus, as scientific contribution in Computer Science, an application development process model and a set of guidelines to supports the developer’s work to create applications for healthcare professionals have been proposed. The proposed model encourages and provides the integration of different contexts of the healthcare professionals, enabling resource appropriation through the perception of abilities and prior knowledge of these professional, and encourages the addition of some new abilities.
Keywords: Model of design process; Healthcare professional; Design based on abilities professional; Natural interaction; Integration of professional; Social and personal contexts; Modelo de processo de design; Profissional da saúde; Design baseado nas habilidades do profissional; Interação natural; Contextos profissional, pessoal e social; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::TEORIA DA COMPUTACAO